Renewable Energy: The Key to Achieving Sustainable Development of Rural Bangladesh (Journal of Chemical Engineering, 2012)
Renewable energy technologies (RETs) can help reduce poverty, energy shortage and environmental degradation such as desertification, biodiversity depletion and climate change effects in Bangladesh. The country is short of gas and electricity supply. Over-exploitation of biomass in meeting energy needs of the rural people has caused environmental degradation. RET can help solve those problems if it is widely used in the rural Bangladesh where people primarily depend on biomass energy. Bangladesh has enough renewable to mitigate such energy crisis and its adverse consequences. Bangladesh being an underdeveloped country, global initiative would be helpful in transferring RETs for the village households. This paper describes the glimpses of RETs in Bangladesh in terms of its policy issues, implementation, dissemination, marketing, and research and development activities. Modern RETs are still in the research, development and demonstration phase in the country. Like most of the developing countries, there is a niche market for new RETs and several private sector entrepreneurs and NGOs have tried to explore this market. DOI: http://dx.doi.org/10.3329/jce.v26i1.10175 JCE 2011; 26(1): 9-15